Sistem Informasi Pendaftaran Mahasiswa Baru Menggunakan Framework Codeigniter dan Application Programming Interface - Harlen Gilbert Simanullang; Arina Prima Silalahi; Darwis Robinson Manalu (ULTIMA InfoSys, 2021)
One of the most important things in the work process is the presentation of information that is fast and accurate. Data is processed in a short time, it will increase work efficiency, one of which is by using the system to process and display data into information. Information systems are needed considering technology is growing and now people are required to use more technology to reduce activities outside the home. Problems that often arise are the tight location of registration and the length of service for one registrant due to filling out registration forms and screening examinations for new students. In addition, the large accumulation of registration and trial files also takes a long time so that announcements of new student graduations cannot be made. The goal is to build a new student admission information system for all faculties at the Indonesian Methodist University, reduce applicants who come to the registration location, reduce the use of paper registration forms, help submit and fill in student data, conduct online screening exams, provide information on new student registration, schedule and payment of tuition fees. The result of this initialization is building a new student registration information system using the Codeigniter Framework and Application Programming Interface (API). Index Terms—Application Programming Interface (API); Codeigniter framework; information systems; online registration